STRAIN ENERGY MAXIMIZATION APPROACH TO THE DESIGN OF FULLY COMPLIANT MECHANISMS USING TOPOLOGY OPTIMIZATION - CARDOSO, EDUARDO LENZ (2004)
THE PAPER PRESENTS AN ALTERNATIVE FORMULATION FOR THE DESIGN OF Â°EXIBLE STRUCTURES AND FULLY COMPLIANT MECHANISMS USING TOPOLOGY OPTIMIZATION. THE KEY TO THIS APPROACH IS THE MAXIMIZATION OF A FUNCTION OF THE STRAIN ENERGY STORED IN THE MECHANISM. THE PROPOSED FORMULATION REDUCES THE APPEARANCE OF COMMON PROBLEMS LIKE INTERMEDIATE DENSITIES, CHECKER BOARD AND 1-NODE HINGES, AND CAN BE EXTENDED TO MULTIPHYSICS AND NON-LINEAR PROBLEMS. THE KINEMATIC BEHAVIOR OF THE FULLY COMPLIANT MECHANISM IS IMPOSED BY A SET OF DISPLACEMENT CONSTRAINTS. THE SENSITIVITIES ARE DERIVED USING AN ADJOINT METHOD AND THE OPTIMIZATION PROB LEM IS SOLVED USING MATHEMATICAL PROGRAMMING. THE PROPERTIES OF THE PROPOSED FORMULATION ARE SHOWN WITH THE AID OF SOME EXAMPLES.